S heparinom povzročena trombocitopenija - HIT - Kozak, Matija (Zdravniški vestnik, 2008)
Background Unfractionated heparin and low-molecular-weight-heparins are commonly prescribed drugs in everyday clinical practice for treatment or prevention of thrombotic diseases. Heparin is used also for providing patency of various catheters. Heparin seldom causes heparin induced thrombocytopenia (HIT) and concomitant activation of coagulation cascade. Activated coagulationcould result in arterial or venous thrombosis. Conclusions Unrecognized HIT could be fatal. In HIT diagnostics regular follow-up of platelet values is important. When platelet number is decreasing, possibility of HIT should be taken into account. After assessment of the clinical scoring system in HIT probable cases specific tests should be done. When HIT is confirmed, patients should be treated with anticoagulants. Cumarins should notbe used at the beginning, but later in patients with confirmed thrombotic event.
Keywords: Adverse Effects; Chemically Induced; diagnostika; Heparin; Hirudin; Therapeutic Use; therapy; Thrombocytopenia; Trombocitopenija; zapleti; zdravljenje